The protective effect of lipid emulsion in preventing bupivacaine-induced mitochondrial injury and apoptosis of H9C2 cardiomyocytes - Zhe Chen; Zhousheng Jin; Yun Xia; Shishi Zhao; Xuzhong Xu; Thomas J. Papadimos; Quanguang Wang (Taylor & Francis Group, 2017)
Lipid emulsion (LE) has been shown to be effective in the resuscitation of bupivacaine-induced cardiac arrest, but the precise mechanism of this action has not been fully elucidated. Pursuant to this lack of information on the mechanism in which LE protects the myocardium during bupivacaine-induced toxicity, we explored mitochondrial function and cell apoptosis. H9C2 cardiomyocytes were used in study. Cells were randomly divided in different groups and were cultivated 6 h, 12 h, and 24 h. The mitochondria were extracted and mitochondrial ATP content was measured, as was mitochondrial membrane potential, the concentration of calcium ion (Ca2+), and the activity of Ca2+-ATP enzyme (Ca2+-ATPase). Cells from groups Bup1000, LE group, and Bup1000LE were collected to determine cell viability, cell apoptosis, and electron microscopy scanning of mitochondrial ultrastructure (after 24 h). We found that LE can reverse the inhibition of the mitochondrial function induced by bupivacaine, regulate the concentration of calcium ion in mitochondria, resulting in the protection of myocardial cells from toxicity induced by bupivacaine.